Antenatal depression, treatment with selective serotonin reuptake inhibitors, and neonatal brain structure: A propensity-matched cohort study. (30th July 2016) - Jha, Shaili C.; Meltzer-Brody, Samantha; Steiner, Rachel J.; Cornea, Emil; Woolson, Sandra; Ahn, Mihye; Verde, Audrey R.; Hamer, Robert M.; Zhu, Hongtu; Styner, Martin; Gilmore, John H.; Knickmeyer, Rebecca C.
Abstract: The aim of this propensity-matched cohort study was to evaluate the impact of prenatal SSRI exposure and a history of maternal depression on neonatal brain volumes and white matter microstructure. SSRI-exposed neonates (n=27) were matched to children of mothers with no history of depression or SSRI use (n=54). Additionally, neonates of mothers with a history of depression, but no prenatal SSRI exposure (n=41), were matched to children of mothers with no history of depression or SSRI use (n=82). Structural magnetic resonance imaging and diffusion weighted imaging scans were acquired with a 3T Siemens Allegra scanner. Global tissue volumes were characterized using an automatic, atlas-moderated expectation maximization segmentation tool. Local differences in gray matter volumes were examined using deformation-based morphometry. Quantitative tractography was performed using an adaptation of the UNC-Utah NA-MIC DTI framework. SSRI-exposed neonates exhibited widespread changes in white matter microstructure compared to matched controls. Children exposed to a history of maternal depression but no SSRIs showed no significant differences in brain development compared to matched controls. No significant differences were found in global or regional tissue volumes. Additional research is needed to clarify whether SSRIs directly alter white matter development or whether this relationship is mediated by depressive symptoms during pregnancy. Highlights: 13% of pregnant women in U.S. report antidepressant use. Effects of antidepressants on the fetal brain are not fully understood. We used MRI to study brain structure in neonates exposed to SSRIs during pregnancy. Neonates exposed to SSRIs in pregnancy exhibit minimal differences in brain volumes. They exhibit widespread changes in white matter microstructure.